Leis de Newton: uma sequência didática para o Ensino Médio fundamentada na teoria da aprendizagem significativa - Silva, Taís Renata Schaeffer da (2018)
The current demands of society point to the need for changes in the educational context, in this sense, emerges the search for to involve students in building their knowledge, enhancing their experiences and previous knowledges – increasing the criticality and dialogue in the classroom. In physics teaching, especially in High School, there are innumerable actions by the teachers to facilitate and qualify the teaching process, bringing the concepts studied in the classroom to the students' daily lives. In this sense, the present study seeks develop, apply and evaluate a didactic proposal based on the Theory of Significant Learning by David Ausubel. The study develops a didactic sequence was structured in eleven meetings for the teaching of Newton's Laws, so to analyze the relevance of the proposal regarding its feasibility . The study presents a guiding question: What are the potenti alities and limits of a didactic sequence based on the Significant Learning Theory to approach Newton's Laws?Seeking to answer these question, the study is characterized as qualitative and use as tools for data collection and evaluation of the feasibilit y of the pre-test proposal, post -test and the Logbook, which are analyzed according to the content analysis, in agreement with the ideas Bardin (2004). The project was conducted in the second semester of 2017 at a public school located in the Municipality of Passo Fundo/RS, with students in the 1st year of high school. In general, the results obtained show the students involvement during the classes, such as the comprehension of the Newton’s laws concepts. This dissertation accompanies an educational product that consists of a material to support teachers, in which the didactic strategies and activities used in the application of the proposal are described , which is available on the EduCapes portal at the address <http://educapes.capes.gov.br/handle/capes/206802>.